Assessing Technology Adoption At A University Of Technology: A Case Study Of Electronic Response System - Tsumake, Onalenna, Pearl (Central University of Technology, Free State, 2020)
Technology adoption is defined as accepting and using a new technology in order to improve delivery, service or performance. One such new technology is an Electronic Response System, called clickers that may be used to leverage classroom participation. ERS is a system that consists of a device used by students in conjunction with an electronic USB transceiver, connected to a personal computer. One of the advantages of ERS is to help passive students become more actively engaged with course material during classroom time, while helping academics to monitor student learning. Despite the advantages of using ERS in education, some academics fail to adopt this new technology into their teaching practice. This study aims to present factors that may help to promote the use and adoption of an ERS at a University of Technology. A non-experimental research design, incorporating a descriptive case study with quantitative data is used with convenient sampling. A small-scale preliminary study was undertaken in order to test the questionnaire as the main data collection instrument. A convenient sample of 20 academics from the Central University of Technology participated in this. A total of 57 academics then participated in the main study, using a questionnaire structured around the four main constructs of Venkatesh’s Unified Theory of Acceptance and Use of Technology (UTAUT) model. The four constructs are Performance Expectancy, Effort Expectancy, Facilitating Conditions and Social Influence. Performance Expectancy is the level to which an individual believes that using the system will help him or her to achieve achievements in job performance. Effort Expectancy is defined by the level of ease regarding the use of technology sustained in systems. Social Influence is defined as the level to which an individual perceives the importance of a technology, based on the perceptions of others. Facilitating Conditions refers to the extent to which a person perceives that a technical and organizational infrastructure is available for the intended system. The UTAUT model aims to explain user intentions to use an information system. The main advantage of this model is that it focuses on user behaviour towards new technologies. Three of the four variables in the UTAUT model were selected, being age, experience and gender. The fourth variable, voluntariness of use, was not included as it is associated with mandatory use of a new technology. This is not applicable to this study as academics have the freedom to choose whether to adopt ERS or not, into their teaching practice. Statistical results suggest that there is a strong relationship between Performance Expectancy, Effort Expectancy and Facilitating Conditions towards the use of ERS. Social Influence has a moderate relationship in this regard. The results also indicate that age, experience or gender, play no significant role in the adoption of such a system. Based on these results, there is a need to create awareness among all academics, irrespective of their age, experience or gender, of the importance of adopting ERS in their teaching practice to further student learning.
Dissertation